2009
DOI: 10.1002/bit.22549
|View full text |Cite
|
Sign up to set email alerts
|

CHO gene expression profiling in biopharmaceutical process analysis and design

Abstract: Increase in both productivity and product yields in biopharmaceutical process development with recombinant protein producing mammalian cells can be mainly attributed to the advancements in cell line development, media, and process optimization. Only recently, genome-scale technologies enable a system-level analysis to elucidate the complex biomolecular basis of protein production in mammalian cells promising an increased process understanding and the deduction of knowledge-based approaches for further process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 24 publications
(37 reference statements)
2
36
0
Order By: Relevance
“…Previous microarray expression profiling studies focussing on productivity in CHO Schaub et al, 2010;Trummer et al, 2008;Kantardjieff et al, 2010;Yee et al, 2007) and in the commercially used mouse myeloma NS0 cell line (Charaniya et al, 2009;Khoo et al, 2007;Seth et al, 2007) have identified several crucial pathways and processes. These microarray-based productivity studies have also been complemented by proteomics studies in CHO (Carlage et al, 2009;Meleady et al, 2008;Nissom et al, 2006) and NS0 Smales et al, 2004;Alete et al, 2005;Dinnis et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Previous microarray expression profiling studies focussing on productivity in CHO Schaub et al, 2010;Trummer et al, 2008;Kantardjieff et al, 2010;Yee et al, 2007) and in the commercially used mouse myeloma NS0 cell line (Charaniya et al, 2009;Khoo et al, 2007;Seth et al, 2007) have identified several crucial pathways and processes. These microarray-based productivity studies have also been complemented by proteomics studies in CHO (Carlage et al, 2009;Meleady et al, 2008;Nissom et al, 2006) and NS0 Smales et al, 2004;Alete et al, 2005;Dinnis et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Such large-scale datasets would enable both a detailed analysis of a specific phenotype of a certain cell clone (e.g. cell-specific productivity) and a comprehensive molecular picture of the cellular responses to environmental changes such as a change in the composition of cell culture media (14). Thus, these data could greatly help to improve cell lines and production processes to finally obtain high recombinant product concentrations of correctly glycosylated antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…This intensity based approach for filtering is commonly used [26] and a threshold of 50-100 is typical in the literature [27,28]. This step led to the reduction of relevant probes from 45,101 to 15,742 with a signal distinguishable from noise.…”
Section: Noise Reduction From Normalized Gene Expression Datamentioning
confidence: 98%